Analysis of Maqāṣid al-Sharī’ah on the Protection of Children’s Rights Following Divorce - Aminudin Aminudin; Nawir Yuslem; Iqbal Irham (JURNAL AKTA, 2026)
This study aims to analyze the protection of children’s rights following divorce by employing the framework of Maqāṣid Sharī’ah as a normative and philosophical foundation within Islamic law. Divorce is a social phenomenon that not only affects the marital relationship between spouses but also generates serious consequences for the fulfillment and protection of children’s rights. In many cases, children become the most vulnerable parties, suffering psychological, economic, and social harm as a result of the dissolution of their parents’ marriage. Therefore, the protection of children’s rights after divorce constitutes a crucial issue that requires comprehensive examination, including from the perspective of Islamic law through the Maqāṣid Sharī’ah approach. This research adopts a qualitative methodology with a normative-juridical approach. Data were collected through library research on primary and secondary sources, including the Qur’an, Hadith, classical fiqh texts, statutory regulations related to child protection, as well as relevant scholarly literature. Data analysis was conducted by linking the concept of post-divorce child rights protection to the fundamental objectives of Maqāṣid al-Sharī‘ah, namely the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). The findings indicate that the protection of children’s rights after divorce is strongly aligned with the principles of Maqāṣid al-Sharī‘ah, particularly in safeguarding children’s survival, well-being, and optimal development. The protection of children’s rights following divorce constitutes both a al-sharī’ah-based and humanitarian imperative and serves as a key indicator of justice within Islamic family law, as Maqāṣid al-Sharī’ah must be oriented toward human welfare and quality-of-life development (human development).